2022
DOI: 10.1002/ep.13979
|View full text |Cite
|
Sign up to set email alerts
|

A state‐of‐the‐art review of the fate of heavy metals and product properties from pyrolysis of heavy‐metal(loid)‐enriched biomass harvested from phytoextraction

Abstract: Vegetation has successfully been used for cleaning up metal(loid) polluted water bodies and lands through extracting and accumulating of contaminants in their aboveground biomass (phytoextraction). As this remediation technique is approaching extensive demonstration scale application and potential commercialisation, research efforts have been investigating new ways to achieve valorization of its by-products, the heavy-metal-enriched biomass (HMEB). Biomass pyrolysis as an energy conversion technique represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…Lignocellulose biomass is a renewable low cost raw material that can be used to generate many bio-fuels, bio-materials, and biochemicals. [1][2][3][4][5] The high value utilization of lignocellulose waste is considered to be of great significance for reducing carbon emissions and achieving sustainable development. 2,5 Currently, the biochemical pathway is one of the most widely used technologies for the production of biofuels and bio-chemicals, especially for the production of bio-ethanol, bio-butanol, acetone/butanol/ethanol (ABE), and bio-gas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lignocellulose biomass is a renewable low cost raw material that can be used to generate many bio-fuels, bio-materials, and biochemicals. [1][2][3][4][5] The high value utilization of lignocellulose waste is considered to be of great significance for reducing carbon emissions and achieving sustainable development. 2,5 Currently, the biochemical pathway is one of the most widely used technologies for the production of biofuels and bio-chemicals, especially for the production of bio-ethanol, bio-butanol, acetone/butanol/ethanol (ABE), and bio-gas.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The high value utilization of lignocellulose waste is considered to be of great significance for reducing carbon emissions and achieving sustainable development. 2,5 Currently, the biochemical pathway is one of the most widely used technologies for the production of biofuels and bio-chemicals, especially for the production of bio-ethanol, bio-butanol, acetone/butanol/ethanol (ABE), and bio-gas. [6][7][8] It has been shown that lignocellulose-based ABE, generated by enzymolysis and fermentation of lignocellulosic waste, can be utilized as intermediates to produce bio-fuels or high value-added chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation